A Rare Presentation of Small Bowel Diverticulosis Causing Chronic Obstruction and Malnutrition: A Case Study with Review of Literature - Y. Mathangasinghe; U. M. J. E. Samaranayake; J. D. Jayasinghe; A. S. K. Banagala (Case Reports in Surgery)
Small bowel diverticulosis is an uncommon entity. Clinical presentation of small intestinal diverticulosis is variable. A high mortality is associated with complications such as chronic malnutrition, haemorrhage, intestinal obstruction, and perforation. We report a case of a 63-year-old female with multiple small bowel diverticuli spanning from the first part of the duodenum to the proximal ileum presenting with chronic malnutrition and subacute intestinal obstruction. Although exploratory laparotomy was performed, we opted for a totally conservative treatment in order to avoid complications such as short gut syndrome and anastomotic leakage.